Birth Order, Schooling, and Earnings - Behrman, Jere R.; Taubman, Paul (Journal of Labor Economics, 1986)
"Birth-order effects are posited by many to affect earnings and schooling. We show how such effects can be interpreted to shift either the earnings possibility frontier for siblings or parental preferences. We find empirical evidence for birth-order effects on (age-adjusted) schooling and on earnings for young U.S. adults, though the latter is not robust for all specifications. The examination of intrahousehold allocations suggests that these birth-order differences occur despite parental preferences or prices by birth order favoring later borns, apparently because of stronger endowment effects that favor first borns."